A kind of high-purity nano-spherical aluminum oxide and preparation method thereof

By heating and stirring the aluminum hydroxide slurry, solid-liquid separation, drying, crushing, depolymerization and calcination, high-purity nano-like spherical alumina is prepared, which solves the problem of unstable preparation process and high cost in the existing technology. Problem, nano-alumina with high purity, high activity and low specific surface area has been achieved, which is suitable for industrial applications.

CN117800372BActive Publication Date: 2025-01-21NINGBO GUOFENG NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410006579.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-03
Publication Date
2025-01-21
Estimated Expiration
2044-01-03

AI Technical Summary

Technical Problem

In the prior art, the preparation method of nanospherical alumina has problems such as unstable process, high cost, low yield and high industrial difficulty, making it difficult to achieve high purity, low specific surface area and high activity nanoalumina.

Method used

High-purity nano-spherical alumina is prepared by using aluminum hydroxide slurry through heating and stirring, solid-liquid separation, drying, crushing, depolymerization and calcination. This method uses high-temperature and high-pressure operation to recrystallize the aluminum hydroxide solution, dry it to drain out the water, pulverize, depolymerize and refine the particles, and calcine and phase invert to control the specific surface area.

Benefits of technology

Nano-like spherical alumina with high purity, high activity and low specific surface area has been achieved, with controllable process, good reproducibility and low cost, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117800372B_ABST
    Figure CN117800372B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of nanomaterial preparation, and discloses a method for preparing high-purity nano-spherical alumina, comprising the following steps: (1) taking aluminum hydroxide slurry, heating and stirring the reaction, and then performing solid-liquid separation to obtain powder; (2) drying the powder, crushing and depolymerizing the powder, and then performing solid-liquid separation to obtain ultrafine alumina powder; (3) calcining the ultrafine alumina powder to obtain high-purity nano-spherical alumina. The raw materials of the present invention are widely available, easy to obtain and convenient to store, the preparation process is controllable, reproducible, low cost, easy to realize industrialization, and the prepared high-purity ultrafine spherical alumina has high activity and low specific surface area, and can be widely used in various industries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano material preparation, in particular to a high-purity nano spherical aluminum oxide and a preparation method thereof. Background Art

[0002] With the development of high technology, society pays more and more attention to new materials. Workers at home and abroad pay great attention to the development and application of new materials, and various materials with special functions are also valued by people. High-purity ultrafine alumina has fine structure, uniform organization, specific grain boundary structure, high temperature stability and good processing performance, heat insulation and heat resistance, and can be combined with a variety of materials. It is mainly used in the electronics industry, biochemical ceramics, structural ceramics, functional ceramics, etc. It is one of the basic materials in high-tech fields such as electronics, machinery, aviation, chemical industry, and building materials.

[0003] At present, the preparation methods of nano spherical alumina mainly include sol-gel method, precipitation method, microemulsion method, explosion method, etc. Among them, the sol-gel method has the characteristics of high powder purity and uniformity, but due to the use of organic solvents and surfactants, it has the disadvantage of being unfavorable for the separation and drying of alumina powder; the precipitation method can prepare nano alumina powder with very good sphericity, uniform morphology, and narrow particle size distribution, but this method has great limitations and the morphology formation mechanism is still unclear; the particles obtained by the microemulsion method have small particle size, uniform distribution, high stability, and good repeatability, but due to the excessive fineness of the product particles, solid-liquid separation is difficult to carry out, and the filtration and centrifugation effects are not good; the unconventional explosion method has the advantage of fast synthesis reaction speed compared with the conventional method for preparing nano alumina, so more and more researchers have begun to use this method to prepare nano materials, but the explosion method has high production cost, low output, high industrialization difficulty, it cannot be finely controlled, the product quality is unstable, the nano spherical alumina produced has low activity, the application direction is relatively single, and it has great danger, the combustion temperature is not easy to control, and the product collection is also difficult.

[0004] Therefore, how to provide a method for preparing high-purity nano-spherical alumina with controllable process, good reproducibility and low cost is an urgent problem to be solved. Summary of the invention

[0005] In view of this, the first object of the present invention is to provide a method for preparing high-purity nano-spherical alumina, which has a wide source of raw materials, controllable process, good reproducibility and low cost;

[0006] The second purpose is to provide a high-purity nano-spherical alumina with low specific surface area, high activity and high purity.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The first object of the present invention is to provide a method for preparing high-purity nano-spherical alumina, comprising the following steps:

[0009] (1) taking aluminum hydroxide slurry, heating and stirring the reaction, and then performing solid-liquid separation to obtain powder;

[0010] (2) drying, crushing and depolymerizing the powder and then separating the solid from the liquid to obtain ultrafine alumina powder;

[0011] (3) calcining the ultrafine alumina powder to obtain high-purity nano-spherical alumina.

[0012] Preferably, in the above-mentioned method for preparing high-purity nano-spherical alumina, the method for preparing high-purity nano-spherical alumina is characterized in that the preparation method of the aluminum hydroxide slurry in step (1) is as follows: aluminum hydroxide and water are evenly mixed to obtain an aluminum hydroxide solution, a dispersant is added to the aluminum hydroxide solution, and the pH is adjusted to 9-11 after sand grinding to obtain an aluminum hydroxide slurry.

[0013] Preferably, in the above-mentioned method for preparing high-purity nano-spherical alumina, the aluminum hydroxide meets the following conditions: D50≤30um, D10>0.5um, D90≤60um; BET≤50㎡ / g; AL(OH)3 content≥99.99%.

[0014] Preferably, in the above-mentioned method for preparing high-purity nano-spherical aluminum oxide, the solid content of the aluminum hydroxide solution is 20-60%;

[0015] The added amount of the dispersant is 0.3-2% of the mass of aluminum hydroxide;

[0016] The dispersant is an ammonium salt organic additive, and the ammonium salt organic additive includes any one or more of ammonium chloride, ammonium sulfate, ammonium carbonate, ammonium bisulfate, ammonium nitrate, alkyl trimethyl ammonium salt, alkyl dimethyl benzyl ammonium salt, dodecyl dimethyl benzyl ammonium chloride, alkyl dimethyl hydroxyethyl quaternary ammonium salt, octadecyl dimethyl hydroxyethyl ammonium nitrate, and octadecyl dimethyl hydroxyethyl ammonium perchlorate.

[0017] Preferably, in the above-mentioned method for preparing high-purity nano-spherical alumina, the temperature of the heating and stirring reaction in step (1) is 180-300° C., and the time is 24-72 hours;

[0018] The heating and stirring reaction is controlled at a pressure of 0.5-3 MPa.

[0019] Preferably, in the above method for preparing high-purity nano-spherical alumina, the drying temperature in step (2) is 650-900°C.

[0020] Preferably, in the above-mentioned method for preparing high-purity nano-spherical alumina, the drying is gradient drying, specifically:

[0021] Raise the temperature from 30-50℃ to 350-450℃ at a rate of 2-4℃ / min and keep it at constant temperature for 1h;

[0022] Continue to increase the temperature from 350-450°C to 640-890°C at a rate of 3-5°C / min;

[0023] Continue to increase the temperature from 640-890℃ to 650-900℃ within 40-80min at a rate of 0.1-0.2℃ / min, and keep the temperature constant for 3h.

[0024] Finally, the temperature was lowered from 650-900°C to 60-90°C at a rate of 2-4°C / min.

[0025] Preferably, in the above method for preparing high-purity nano-spherical alumina, the calcination temperature in step (3) is 950-1300°C.

[0026] Preferably, in the above-mentioned method for preparing high-purity nano-spherical alumina, the calcination is a gradient calcination, specifically:

[0027] Raise the temperature from 30-50℃ to 700-800℃ at a rate of 5-7℃ / min and keep it constant for 1h;

[0028] Continue to increase the temperature from 700-800℃ to 1250-1300℃ at a rate of 2-4℃ / min, and keep the temperature constant for 2h;

[0029] Finally, the temperature was lowered from 1250-1300°C to 60-80°C at a rate of 4-6°C / min.

[0030] The second object of the present invention is to provide a high-purity nano-spherical alumina prepared by any of the above methods.

[0031] The present invention provides a high-purity nano-spherical aluminum oxide and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:

[0032] In the preparation process of the high-purity nano-spherical aluminum oxide of the present invention, high temperature and high pressure operation can make the aluminum hydroxide solution recrystallize, and change the irregular morphology into a regular morphology, so that the grains are finer and more uniform, and the surface area is reduced; the drying operation can discharge the physical water and crystal water of the aluminum hydroxide, and the growth of the aluminum oxide grains can be controlled by controlling the drying temperature; the pulverization and depolymerization operation can make the grains finer again, so that each single spherical particle is evenly dispersed; the calcination operation can obtain α-phase aluminum oxide, and the specific surface area can be adjusted by controlling the temperature change.

[0033] The raw materials of the present invention are widely available, easily obtainable and convenient to store; the preparation process is controllable, reproducible and low-cost, and it is easy to industrialize; and the prepared high-purity ultrafine spherical alumina has high activity and low specific surface area, and can be widely used in various industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0035] Figure 1 It is a schematic diagram of the particle size analysis results of the powder of the present invention;

[0036] Figure 2 This is a schematic diagram of the electron microscopy morphology of the powder of the present invention;

[0037] Figure 3 This is a schematic diagram of the particle size analysis results of the lithium hydroxide powder after drying according to the present invention;

[0038] Figure 4 This is a schematic diagram of the electron microscopy results of the lithium hydroxide powder after drying of the present invention;

[0039] Figure 5 It is a schematic diagram of the particle size analysis results of the high-purity nano-spherical aluminum oxide of the present invention;

[0040] Figure 6 This is a schematic diagram of the electron microscope morphology of the high-purity nano-spherical aluminum oxide of the present invention;

[0041] Figure 7 This is a BET test result diagram of the high-purity nano-spherical aluminum oxide of the present invention;

[0042] Figure 8 This is a crystal phase diagram of the high-purity nano-spherical aluminum oxide of the present invention. DETAILED DESCRIPTION

[0043] Embodiments of the present invention are described in detail below, and the examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals represent the same or similar elements or elements with the same or similar functions from beginning to end. The embodiments described below by reference to the accompanying drawings are exemplary, are only used to explain the present invention, and are not to be construed as limitations of the present invention. In the embodiments, if specific techniques or conditions are not indicated, the techniques or conditions described in the literature in this area or the product specifications are carried out. The reagents used or the instruments that are not indicated by the manufacturer are all conventional products that can be obtained commercially.

[0044] In one aspect of the present invention, the present invention provides a method for preparing high-purity nano-spherical aluminum oxide, comprising the following steps:

[0045] S100. Aluminum hydroxide and water are uniformly mixed to obtain an aluminum hydroxide solution, a dispersant is added to the aluminum hydroxide solution, and the pH is adjusted to 9-11 after sand milling to obtain aluminum hydroxide slurry.

[0046] In this step, the aluminum hydroxide meets the following conditions: D50≤30um, D10>0.5um, D90≤60um; BET≤50㎡ / g; AL(OH)3 content≥99.99%.

[0047] Furthermore, the solid content of the aluminum hydroxide solution is 20-60%, for example, it can be 20%, 30%, 40%, 50%, 60%, etc. The higher the solid content, the smaller the gaps between particles, and the more difficult it is to refine the particles after arrangement; in addition, pH is an important factor affecting the morphology and structure of the particles after the reaction. The higher the pH value, the more regular the grain development and the smaller the grains.

[0048] The amount of the dispersant added is 0.3-2% of the mass of aluminum hydroxide, preferably 0.5-1.5%, for example, 0.5%, 1.0%, 1.5%, etc.; the dispersant is an ammonium salt organic auxiliary agent, and the ammonium salt organic auxiliary agent includes quaternary ammonium salts, primary, secondary and tertiary ammonium salts, wherein the primary, secondary and tertiary ammonium salts include any one or more of ammonium chloride, ammonium sulfate, ammonium carbonate, ammonium bisulfate, ammonium nitrate, etc., and the quaternary ammonium salts include any one or more of alkyl trimethyl quaternary ammonium salts, alkyl dimethyl benzyl quaternary ammonium salts, dodecyl dimethyl benzyl ammonium chloride, alkyl dimethyl hydroxyethyl quaternary ammonium salts, octadecyl dimethyl hydroxyethyl ammonium nitrate, octadecyl dimethyl hydroxyethyl ammonium perchlorate, etc. The addition of the dispersant is to form a repulsive force between particles according to the double charge theory, thereby increasing steric hindrance; the fine particles formed by aluminum hydroxide after the hydrothermal synthesis reaction are not easy to form agglomerates under the action of the dispersant.

[0049] The sand milling is to grind the powder to a particle size less than 0.5 μm, which can increase the surface area of ​​the powder particles, make the particles more uniform after hydrothermal synthesis, and improve the reaction efficiency.

[0050] Through the treatment in this step, the surface area of ​​aluminum hydroxide can be increased, so that the subsequent synthesis reaction can be carried out more fully and completely.

[0051] S200. Take aluminum hydroxide slurry, heat and stir to react, then perform solid-liquid separation to obtain powder.

[0052] Specifically, this step is carried out in a reactor, and the reactor can be heated by heat-conducting oil, and the heating temperature is 180-300°C, preferably 200-280°C, for example, 200°C, 230°C, 250°C, 280°C, etc.; at the same time, pressure is applied to the reactor, and the pressure in the reactor is controlled at 0.5-3MPa, for example, 0.5MPa, 1MPa, 2MPa, 3MPa, etc.; the slurry in the reactor is stirred by a stirring blade to make it fully react, and the entire reaction time is controlled at 24-72h, for example, 24h, 36h, 48h, 72h, etc.; the slurry obtained after the reaction is separated into solid and liquid by a filter press, and the obtained powder particle size D10>0.04um, D50≤0.1um, D90<0.25um, BET<5㎡ / g, such as Figure 1 Shown is a schematic diagram of particle size analysis of the powder of the present invention.

[0053] Specifically, in this step, the effects of reaction temperature, pressure, time, etc. on powder particle size are shown in Table 1-3:

[0054] Table 1 Effect of reaction temperature on particle size

[0055]

[0056] Table 2 Effect of reaction pressure on particle size

[0057]

[0058] Table 3 Effect of reaction time on particle size

[0059]

[0060] In this step, the aluminum hydroxide trihydrate solution can be recrystallized by high temperature and high pressure conditions in the reactor, and the irregular morphology is recrystallized into a regular morphology, and the obtained grains are small and uniform, and the surface area is reduced. Figure 2 Shown is a schematic diagram of the electron microscope morphology of the powder of the present invention.

[0061] S300. Drying, crushing, deagglomerating and then separating the solid from the liquid to obtain ultrafine alumina powder.

[0062] In this step, a roller kiln is preferably used to dry the powder, and the drying temperature is 650-900°C; preferably, the drying is gradient drying, specifically: heating from 30-50°C to 350-450°C at a rate of 2-4°C / min, and keeping the temperature constant for 1h; continuing to heat from 350-450°C to 640-890°C at a rate of 3-5°C / min; continuing to heat from 640-890°C to 650-900°C within 40-80min at a rate of 0.1-0.2°C / min, keeping the temperature constant for 3h, and finally cooling from 650-900°C to 60-90°C at a rate of 2-4°C / min.

[0063] The drying process is the process of aluminum hydroxide expelling physical water and crystallization water. In this process, aluminum hydroxide decomposes into aluminum oxide powder. The drying temperature gradient curve controls the growth of aluminum oxide grains and maintains smaller grains. If the drying temperature exceeds 900°C, the grains will grow rapidly. Under high temperature conditions, the grains will agglomerate, and small particles will agglomerate into large particles. The large particles formed under high temperature are hard agglomerates, which are difficult to break by physical methods.

[0064] After drying in the above steps, alumina powder is obtained, and the particle size distribution of the powder is D10<0.5um, D50≤2.2um, D90<13um, BET≤50㎡ / g, and the morphology is close to spherical. Figure 3-4 Shown are the particle size analysis and electron microscope morphology of aluminum oxide after drying.

[0065] Furthermore, the alumina powder obtained after drying is crushed and deagglomerated using a sand mill, and the obtained slurry D50≤100nm is obtained. After the slurry is separated into solid and liquid by a filter press, ultrafine alumina powder containing a small amount of water is obtained. The dried alumina will form agglomerates under the action of van der Waals force, polar molecules and temperature. The purpose of crushing and deagglomeration is to make the grains smaller again so that each single spherical particle is evenly dispersed.

[0066] S400. calcining the ultrafine alumina powder to obtain high-purity nano-spherical alumina.

[0067] In this step, a roller kiln is preferably used to calcine the ultrafine alumina powder, and the calcination temperature is 950-1300°C. Preferably, the calcination is a gradient calcination, specifically: heating from 30-50°C to 700-800°C at a rate of 5-7°C / min, and keeping the temperature constant for 1h; continuing to heat from 700-800°C to 1250-1300°C at a rate of 2-4°C / min, and keeping the temperature constant for 2h; finally, cooling from 1250-1300°C to 60-80°C at a rate of 4-6°C / min, and obtaining high-purity ultrafine nano-spherical alumina powder after calcination.

[0068] In the present invention, if the calcination temperature exceeds 1300°C, the powder will form agglomerates and grow from small particles to large particles; in addition, by extending the insulation time within a suitable temperature range, the full development of the grains can be promoted, and the fuller the crystal development, the smaller the specific surface area.

[0069] During calcination, the spherical alumina is converted into α-alumina, and the specific surface area can be adjusted and controlled. Figure 5-6 As shown, the final high-purity ultrafine nano-spherical alumina powder has the following indicators: BET: 10-40㎡ / g, AL2O3≥99.99%, crystal phase: α-AL2O3, and spherical morphology.

[0070] The detailed data of BET test are shown in Table 4:

[0071] Table 4

[0072]

[0073] The results in Table 4 show that the high-purity ultrafine nano-spherical alumina powder prepared by the present invention has a relatively moderate specific surface area and maintains good activity.

[0074] In addition, the present invention also conducted crystal phase analysis and I CP-OES analysis on the prepared high-purity nano-spherical alumina, and the results are shown in Figure 8 And Table 5.

[0075] Table 5

[0076]

[0077] It can be seen from Table 5 that the high-purity nano-spherical alumina prepared by the present invention has high purity and low impurity content, so it has high activity and a wider range of applications. For example, high-purity products can be used for surface treatment of semiconductor chips and low-temperature ceramicization in the high-end ceramic industry, thereby reducing downstream processing difficulty and production costs, and can also be used in the sapphire industry, aluminum nitride industry, thermal conductivity and heat dissipation industry, etc.

[0078] It should be noted that the present invention Figure 1-8 The results and data in Tables 4-5 are all test averages of high-purity ultrafine nano-spherical alumina prepared through multiple tests based on the protection scheme of the present invention.

[0079] In another aspect of the present invention, the present invention provides a high-purity nano-spherical aluminum oxide, which is prepared by the method described above. Therefore, the high-purity nano-spherical aluminum oxide has all the characteristics and advantages of the method described above, which will not be repeated here. In general, the high-purity nano-spherical aluminum oxide has a small particle size and has high purity and activity.

[0080] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.

[0081] It should be noted that, unless otherwise specified in the following embodiments and comparative examples, the raw material aluminum hydroxide is high-purity aluminum hydroxide from the same procurement source, satisfying the following conditions: D50≤30um, D10>0.5um, D90≤60um; BET≤50㎡ / g; AL(OH)3 content≥99.99%.

[0082] Example 1

[0083] The preparation method of a high-purity nano-spherical aluminum oxide in this embodiment is as follows:

[0084] (1) aluminum hydroxide and pure water are uniformly mixed to a solid content of 50%, 1% hexadecyltrimethylammonium bromide is added, and the aluminum hydroxide is processed using a sand mill to obtain an aluminum hydroxide slurry;

[0085] (2) adding aluminum hydroxide slurry into a reactor, adjusting the pH of the slurry to 9-11, heating the reactor with heat transfer oil, heating the reactor to 250° C., applying pressure to the reactor, controlling the pressure in the reactor to 1.8 MPa, stirring the slurry in the reactor to allow it to react fully, and controlling the entire reaction time to 50 h. After the reaction, the slurry can be separated into solid and liquid by a filter press to obtain a powder;

[0086] (3) drying the powder in a roller kiln, heating the powder from 40°C to 400°C at a rate of 3°C / min, and keeping the temperature constant for 1 hour; continuing to heat the powder from 400°C to 640°C at a rate of 4°C / min; continuing to heat the powder from 640°C to 650°C at a rate of 0.17°C / min, and keeping the temperature constant for 3 hours; finally, cooling the powder from 650°C to 80°C at a rate of 3.2°C / min, and drying the powder to obtain spherical alumina powder;

[0087] (4) The dried alumina powder is crushed and depolymerized using a sand mill to obtain a slurry, and the slurry is separated into solid and liquid by a filter press to obtain ultrafine alumina powder containing a small amount of water;

[0088] (5) The ultrafine alumina powder is calcined and phase-transformed in a roller kiln. The temperature is increased from 40°C to 750°C at a rate of 5.9°C / min and kept at a constant temperature for 1 hour. The temperature is then increased from 750°C to 1250°C at a rate of 2.8°C / min and kept at a constant temperature for 2 hours. Finally, the temperature is decreased from 1250°C to 70°C at a rate of 5°C / min. After calcination, high-purity ultrafine nano-spherical alumina powder is obtained.

[0089] Example 2

[0090] The preparation method of a high-purity nano-spherical aluminum oxide in this embodiment is as follows:

[0091] (1) aluminum hydroxide and pure water are uniformly mixed to a solid content of 20%, 0.3% hexadecyltrimethylammonium chloride is added, and the aluminum hydroxide is processed using a sand mill to obtain an aluminum hydroxide slurry;

[0092] (2) adding aluminum hydroxide slurry into a reactor, adjusting the pH of the slurry to 9-11, heating the reactor with heat transfer oil at a temperature of 300° C., applying pressure to the reactor, controlling the pressure in the reactor at 3 MPa, stirring the slurry in the reactor to allow it to react fully, and controlling the entire reaction time to 24 h. After the reaction, the slurry can be separated into solid and liquid by a filter press to obtain a powder;

[0093] (3) drying the powder in a roller kiln, heating the powder from 30°C to 350°C at a rate of 2°C / min, and keeping the temperature constant for 1 hour; continuing to heat the powder from 350°C to 660°C at a rate of 3°C / min; continuing to heat the powder from 660°C to 670°C at a rate of 0.1°C / min, and keeping the temperature constant for 3 hours; finally, cooling the powder from 670°C to 60°C at a rate of 2°C / min, and drying the powder to obtain spherical alumina powder;

[0094] (4) The dried alumina powder is crushed and depolymerized using a sand mill to obtain a slurry, and the slurry is separated into solid and liquid by a filter press to obtain ultrafine alumina powder containing a small amount of water;

[0095] (5) The ultrafine alumina powder is calcined and phase-transformed in a roller kiln. The temperature is increased from 30°C to 700°C at a rate of 5°C / min and kept at a constant temperature for 1 hour. The temperature is then increased from 700°C to 1270°C at a rate of 2°C / min and kept at a constant temperature for 2 hours. Finally, the temperature is decreased from 1270°C to 60°C at a rate of 4°C / min. After calcination, high-purity ultrafine nano-spherical alumina powder is obtained.

[0096] Example 3

[0097] The preparation method of a high-purity nano-spherical aluminum oxide in this embodiment is as follows:

[0098] (1) Aluminum hydroxide and pure water are uniformly mixed to a solid content of 60%, 2% hexadecyltrimethylammonium sulfate is added, and the aluminum hydroxide is processed using a sand mill to obtain an aluminum hydroxide slurry;

[0099] (2) adding aluminum hydroxide slurry into a reactor, adjusting the pH of the slurry to 9-11, heating the reactor with heat transfer oil at a temperature of 180° C., applying pressure to the reactor, controlling the pressure in the reactor at 0.5 MPa, stirring the slurry in the reactor to allow it to react fully, and controlling the entire reaction time at 72 h. After the reaction, the slurry can be separated into solid and liquid by a filter press to obtain a powder;

[0100] (3) drying the powder in a roller kiln, heating the powder from 50°C to 450°C at a rate of 4°C / min, and keeping the temperature constant for 1 hour; then heating the powder from 450°C to 890°C at a rate of 5°C / min; then heating the powder from 890°C to 900°C at a rate of 0.2°C / min, and keeping the temperature constant for 3 hours; finally, cooling the powder from 900°C to 90°C at a rate of 4°C / min, and drying the powder to obtain spherical alumina powder;

[0101] (4) The dried alumina powder is crushed and depolymerized using a sand mill to obtain a slurry, and the slurry is separated into solid and liquid by a filter press to obtain ultrafine alumina powder containing a small amount of water;

[0102] (5) The ultrafine alumina powder is calcined and phase-transformed in a roller kiln. The temperature is increased from 50°C to 800°C at a rate of 7°C / min and kept at a constant temperature for 1 hour. The temperature is then increased from 800°C to 1300°C at a rate of 4°C / min and kept at a constant temperature for 2 hours. Finally, the temperature is decreased from 1300°C to 80°C at a rate of 6°C / min. After calcination, high-purity ultrafine nano-spherical alumina powder is obtained.

[0103] The specific surface area, average particle size, etc. of the high-purity ultrafine nano-spherical alumina powder prepared in Examples 1-3 were tested. The results are shown in Table 6:

[0104] Table 6

[0105] Specific surface area Average particle size purity Bulk density Liquidity Example 1 16.27 82nm ≥99.99% <![CDATA[0.33g / cm 3 ]]> 9.2s Example 2 14.68 87nm ≥99.99% <![CDATA[0.35g / cm 3 ]]> 8.9s Example 3 12.55 95nm ≥99.99% <![CDATA[0.38g / cm 3 ]]> 8.3s

[0106] It can be analyzed from Table 6 that the spherical alumina powder prepared by the present invention has a lower specific surface area, high purity, good density and good fluidity.

[0107] Comparative Example 1

[0108] Comparative Example 1 provides a method for preparing aluminum oxide, which is basically the same as Example 1, except that the amount of dispersant added is 0.2%.

[0109] Comparative Example 2

[0110] Comparative Example 2 provides a method for preparing aluminum oxide, which is basically the same as Example 1, except that the amount of dispersant added is 2.5%.

[0111] Comparative Example 3

[0112] Comparative Example 3 provides a method for preparing aluminum oxide, which is basically the same as Example 1, except that the dispersant is oxalic acid.

[0113] Comparative Example 4

[0114] Comparative Example 4 provides a method for preparing aluminum oxide, which is basically the same as Example 1, except that step (2) is carried out under normal pressure.

[0115] Comparative Example 5

[0116] Comparative Example 5 provides a method for preparing aluminum oxide, which is basically the same as Example 1, except that step (2) is carried out at a pressure of 0.3 MPa.

[0117] Comparative Example 6

[0118] Comparative Example 6 provides a method for preparing aluminum oxide, which is basically the same as Example 1, except that step (2) is carried out at a pressure of 3.5 MPa.

[0119] Comparative Example 7

[0120] Comparative Example 7 provides a method for preparing aluminum oxide, which is basically the same as Example 1, except that step (4) is not performed, that is, calcination is performed after drying.

[0121] Comparative Example 8

[0122] Comparative Example 8 provides a method for preparing aluminum oxide, which is basically the same as Example 1, except that the drying operation in step (3) is: heating from 40°C to 400°C at a rate of 3°C / min, and keeping the temperature constant for 1 hour; continuing to heating from 400°C to 640°C at a rate of 4°C / min; continuing to heating from 640°C to 650°C at a rate of 0.17°C / min, and naturally cooling to 80°C.

[0123] Comparative Example 9

[0124] Comparative Example 9 provides a method for preparing aluminum oxide, which is basically the same as Example 1, except that the drying operation in step (3) is: heating from 40°C to 650°C at a rate of 3°C / min, keeping the temperature constant for 3 hours, and finally cooling from 650°C to 80°C at a rate of 3.2°C / min.

[0125] Comparative Example 10

[0126] Comparative Example 10 provides a method for preparing aluminum oxide, which is basically the same as Example 1, except that the drying operation in step (3) is: heating from 40°C to 650°C at a rate of 3°C / min, keeping the temperature constant for 3 hours, and then naturally cooling to room temperature.

[0127] Comparative Example 11

[0128] Comparative Example 11 provides a method for preparing aluminum oxide, which is basically the same as Example 1, with the only difference being that the calcination operation in step (5) is: heating from 40°C to 750°C at a rate of 5.9°C / min, and keeping the temperature constant for 1 hour; continuing to heating from 750°C to 1250°C at a rate of 2.8°C / min, and keeping the temperature constant for 2 hours; and finally naturally cooling down to 70°C.

[0129] Comparative Example 12

[0130] Comparative Example 12 provides a method for preparing aluminum oxide, which is basically the same as Example 1, except that the calcination operation in step (5) is: heating from 40°C to 1250°C at a rate of 5.9°C / min, and keeping the temperature constant for 2h; finally, cooling from 1250°C to 70°C at a rate of 5°C / min.

[0131] Comparative Example 13

[0132] Comparative Example 13 provides a method for preparing aluminum oxide, which is basically the same as Example 1, except that the calcination operation in step (5) is: heating from 40°C to 1250°C at a rate of 5.9°C / min, keeping the temperature constant for 2 hours, and then naturally cooling to 70°C.

[0133] The specific surface area, average particle size, etc. of the high-purity ultrafine nano-spherical alumina powder prepared in Comparative Examples 1-13 were tested. The results are shown in Table 7:

[0134] Table 7

[0135] Specific surface area Average particle size purity Bulk density Liquidity Comparative Example 1 6.79㎡ / g 79nm ≥99.99% / / Comparative Example 2 5.63㎡ / g 75nm ≥99.99% / / Comparative Example 3 15.38㎡ / g 152nm ≥99.99% / / Comparative Example 4 42㎡ / g 450nm ≥99.99% / / Comparative Example 5 35㎡ / g 196nm ≥99.99% / / Comparative Example 6 4.31㎡ / g 98nm ≥99.99% / / Comparative Example 7 16.27㎡ / g 626nm ≥99.99% <![CDATA[0.33g / cm 3 ]]> 9.2s Comparative Example 8 36.73㎡ / g 82nm ≥99.99% <![CDATA[0.33g / cm 3 ]]> 9.2s Comparative Example 9 22.59㎡ / g 125nm ≥99.99% <![CDATA[0.33g / cm 3 ]]> 9.2s Comparative Example 10 26.46㎡ / g 127nm ≥99.99% <![CDATA[0.33g / cm 3 ]]> 9.2s Comparative Example 11 18.66㎡ / g 86nm ≥99.99% <![CDATA[0.33g / cm 3 ]]> 9.2s Comparative Example 12 20.53㎡ / g 87nm ≥99.99% <![CDATA[0.33g / cm 3 ]]> 9.2s Comparative Example 13 20.75㎡ / g 95nm ≥99.99% <![CDATA[0.33g / cm 3 ]]> 9.2s

[0136] The data of Comparative Examples 1-3 in Table 7 are the test results of aluminum hydroxide powder. The results show that if the amount of dispersant added is too much, the particle size of the powder will become smaller; if other types of dispersants other than ammonium salts are used, the size of aluminum hydroxide particles will be greatly affected. Therefore, it is preferred that the amount of dispersant added is 0.3-2% of the mass of aluminum hydroxide, and the type is preferably an ammonium salt organic additive;

[0137] The data of Comparative Examples 4-6 are the test results of aluminum hydroxide powder. The results show that the particle sizes of aluminum hydroxide slurries obtained at different pressures are different. The particle size of the slurry decreases as the pressure increases, but the relationship between the two is not linear.

[0138] The data of comparative example 7 are the test results of the alumina powder product. The results show that the crushing and deagglomeration process can deagglomerate the dried powder and keep the powder particles in nanometer size;

[0139] The data of comparative examples 8-10 are the test results of alumina powder products. The results show that the purpose of keeping warm at 400°C is to remove the crystal water in the powder. By removing the influence of water molecules, the particles can be prevented from agglomerating due to the influence of polar molecules. If the heating curve is changed, the particle size and specific surface area of ​​the alumina powder will be too large.

[0140] The data from comparative examples 11-13 are the test results of alumina powder products. The results show that 750°C is the phase transition temperature of alumina, and the phase transition is γ-alumina. Keeping warm at this stage can make the grains fully developed and have a small specific surface area. The cooling stage has an impact on controlling the grains, and controlling the temperature drop will not damage the grains. If the calcination heating curve is changed, the specific surface area of ​​the alumina powder will be too large.

[0141] In the description of this specification, the description with reference to the terms "one embodiment", "another embodiment", "yet another embodiment", "some embodiments", "some specific embodiments", "some other specific embodiments" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory. In addition, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated.

[0142] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing high-purity nano-spherical alumina, characterized in that: The following steps are involved: (1) taking aluminum hydroxide slurry, heating and stirring the slurry at a temperature of 180-300°C, a time of 24-72 hours, and a pressure of 0.5-3 MPa, and then performing solid-liquid separation to obtain a powder; (2) drying, crushing, deagglomerating and then separating the solid from the liquid to obtain ultrafine alumina powder; (3) calcining the ultrafine alumina powder to obtain high-purity nano-spherical alumina; The preparation method of the aluminum hydroxide slurry in step (1) is as follows: aluminum hydroxide and water are uniformly mixed to obtain an aluminum hydroxide solution, a dispersant is added to the aluminum hydroxide solution, and the pH is adjusted to 9-11 after sand milling to obtain an aluminum hydroxide slurry; the amount of the dispersant added is 0.3-2% of the mass of the aluminum hydroxide, and the dispersant is selected from hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride or hexadecyltrimethylammonium sulfate; The drying is a gradient drying, specifically: heating from 30-50°C to 350-450°C at a rate of 2-4°C / min, and keeping the temperature constant for 1 hour; continuing to heat from 350-450°C to 640-890°C at a rate of 3-5°C / min; continuing to heat from 640-890°C to 650-900°C within 40-80 minutes at a rate of 0.1-0.2°C / min, and keeping the temperature constant for 3 hours; finally, cooling from 650-900°C to 60-90°C at a rate of 2-4°C / min; The calcination is a gradient calcination, specifically: heating from 30-50°C to 700-800°C at a rate of 5-7°C / min, and keeping the temperature constant for 1 hour; continuing to heat from 700-800°C to 1250-1300°C at a rate of 2-4°C / min, and keeping the temperature constant for 2 hours; finally, cooling from 1250-1300°C to 60-80°C at a rate of 4-6°C / min.

2. The method for preparing high-purity nano-spherical aluminum oxide according to claim 1, characterized in that: The aluminum hydroxide meets the following conditions: D50≤30um, D10>0.5um, D90≤60um; BET≤50㎡ / g; AL(OH)3 content≥99.99%.

3. The method for preparing high-purity nano-spherical alumina according to claim 1 or 2, characterized in that: The solid content of the aluminum hydroxide solution is 20-60%.

4. A high-purity nano-spherical alumina prepared by the method according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Preparation method and application of nano aluminum oxide

    CN107285352A

  • Submicron spherical aluminum oxide as well as preparation method and application thereof

    CN111392752A

  • High-sintering-activity aluminum oxide ceramic powder and preparation method thereof

    CN112745105A